2021
DOI: 10.3390/vaccines9111225
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association between Individualism and Vaccination Resistance against COVID-19 Vaccination among Chinese Adults: Mediations via Perceived Personal and Societal Benefits

Abstract: Background: Vaccination resistance is the key hurdle against herd immunity as it limits the final vaccination coverage. This study investigated the prevalence and factors of COVID-19 vaccination resistance (i.e., those indicating definitely not taking up COVID-19 vaccination), including individualism, perceived personal benefits (PPB) and perceived societal benefits (PSB) of COVID-19 vaccination, and related mechanisms of the association. Methods: A random telephone survey interviewed 395 unvaccinated adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…The latter was comparable to the 25.1% reported in another local study among unvaccinated adults who had been surveyed two months after the beginning of the rollout [17]. People with a low vaccination intention might be hesitating, waiting to see [15], or refusing COVID-19 vaccination firmly [6]. The low prevalence of COVID-19 vaccination intention is a good reminder to the government that the achievement of herd immunity through vaccination in the next six months remains an uphill mission.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The latter was comparable to the 25.1% reported in another local study among unvaccinated adults who had been surveyed two months after the beginning of the rollout [17]. People with a low vaccination intention might be hesitating, waiting to see [15], or refusing COVID-19 vaccination firmly [6]. The low prevalence of COVID-19 vaccination intention is a good reminder to the government that the achievement of herd immunity through vaccination in the next six months remains an uphill mission.…”
Section: Discussionsupporting
confidence: 75%
“…Ongoing health promotion efforts are thus needed for all countries, regardless of their vaccination rates. These groups of unvaccinated people may include individuals who firmly resist COVID-19 vaccination [6] and those who show psychological reactance against health promotion related to vaccination. Research in such unvaccinated groups is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Collectivism was even cited among lay members of the public in qualitative research examining the prevention behaviors of Chinese–Canadians during the early wave of the COVID-19 pandemic (Lee et al, 2021 ) – giving face validity to the hypothesized link between collectivism and prevention behavior. These are further supported with individual-level quantitative research showing that greater collectivism is associated with more support for and uptake of COVID-19 prevention behaviors (Bok, Shum, Harvie, & Lee, 2021 ; Cho, Guo, & Torelli, 2022 ; Lu, Jin, & English, 2021 ; Travaglino & Moon, 2021 ; Yu, Lau, & Lau, 2021 ). Greater collectivism has also been shown to be correlated with fear of COVID-19 (Ahuja, Banerjee, Chaudhary, & Gidwani, 2021 ; Germani, Buratta, Delvecchio, & Mazzeschi, 2020 ).…”
Section: The Role Of Individualism–collectivism In the Covid-19 Pandemicmentioning
confidence: 66%
“…Given the evidence summarized above, it is clear that considering nuanced models of cultural orientations along with personality traits can help isolate the independent relationship of these on COVID-19 prevention; thereby assisting public health leaders in responding to COVID-19 (Bayeh, Yampolsky, & Ryder, 2021 ; Caulkins, 1999 ; Erman & Medeiros, 2021 ; Nair & Selvaraj, 2021 ; Siritzky, Condon, & Weston, 2022 ). This exploratory analyses may be especially beneficial when considering how public health messaging can be best tailored to promote widespread uptake among individuals with diverse personal characteristics and cultural dispositions (Borah, Hwang, & Hsu, 2021 ; Clark, Davila, Regis, & Kraus, 2020 ; Courtney, Felig, & Goldenberg, 2022 ; Kemmelmeier & Jami, 2021 ; Mo & Park, 2021 ; Yu et al, 2021 ). As such, the present exploratory study sought to examine the independent relationships of cultural orientations and personality traits with the uptake of COVID-19 prevention behaviors among people living in Canada.…”
Section: Study Objectivesmentioning
confidence: 99%
“…For example, interventions could be adapted to include other forms of prosocial motivations, such as collectivism (the practice of prioritizing a group over individuals within the group) [ 66 ]. Previous research has shown that collectivism is associated with COVID-19 vaccine acceptance [ 12 , 67 ], while individualism (ie, emphasis on the autonomous individual) is associated with COVID-19 vaccine hesitancy [ 68 ]. Therefore, to override feelings of personal invulnerability to COVID-19 in countries that are more individualistic than collectivistic (eg, Canada, the United States), messages that promote community well-being, highlight shared goals, and induce feelings of interdependence should be used to encourage COVID-19 vaccination [ 69 ].…”
Section: Discussionmentioning
confidence: 99%